Towards Naked Zinc(II) in the Condensed Phase: A Highly Lewis Acidic ZnII Dication Stabilized by Weakly Coordinating Carborate Anions. (24th November 2020) - Adet, Nicolas; Specklin, David; Gourlaouen, Christophe; Damiens, Thibault; Jacques, Béatrice; Wehmschulte, Rudolf J.; Dagorne, Samuel
Abstract: The employment of the hexyl‐substituted anion [HexCB11 Cl11 ] − allowed the synthesis of a Zn II species, Zn[HexCB11 Cl11 ]2, 3, in which the Zn 2+ cation is only weakly coordinated to two carborate counterions and that is soluble in low polarity organic solvents such as bromobenzene. DOSY NMR studies show the facile displacement of at least one of the counterions, and this near nakedness of the cation results in high catalytic activity in the hydrosilylation of 1‐hexene and 1‐methyl‐1cyclohexene. Fluoride ion affinity (FIA) calculations reveal a solution Lewis acidity of 3 (FIA=262.1 kJ mol −1 ) that is higher than that of the landmark Lewis acid B(C6 F5 )3 (FIA=220.5 kJ mol −1 ). This high Lewis acidity leads to a high activity in catalytic CO2 and Ph2 CO reduction by Et3 SiH and hydrogenation of 1, 1‐diphenylethylene using 1, 4‐cyclohexadiene as the hydrogen source. Compound 3 was characterized by multinuclear NMR spectroscopy, mass spectrometry, single crystal X‐ray diffraction, and DFT studies. Abstract : A salt compound containing a formal Zn 2+ dication only stabilized by weakly coordinated carborate anions was first structurally characterized and shown to be soluble in low polarity solvents. Based on its reactivity with alkene, alkyne and in hydrosilylation catalysis, it is a strong Lewis acid, possibly the strongest Zn‐based Lewis acid to date.